Integron detection for prediction of trimethoprim/sulfamethoxazole susceptibility in children with Enterobacterales urinary tract infections. (23rd November 2021) - Elias, Peter; Barraud, Olivier; El Hamel, Chahrazed; Chainier, Delphine; Dallochio, Aymeric; Grélaud, Carole; Ploy, Marie-Cécile; Guigonis, Vincent; Garnier, Fabien
Abstract: Objectives: In some countries, third-generation cephalosporins (3GCs) serve as first-line therapy in children with urinary tract infections (UTIs). However, their use may contribute to the emergence of antibiotic resistance, notably among Gram-negative bacteria (GNB). Integrons are bacterial genetic elements involved in antibiotic resistance in GNB. Their absence is associated with >97% susceptibility to trimethoprim/sulfamethoxazole in adults infected with GNB. The objective of this study was to examine the value of integron detection directly from urine samples as a predictive marker of resistance to trimethoprim/sulfamethoxazole in children with GNB-related UTIs. Methods: Children admitted to the Limoges University Hospital's paediatric emergency department between February 2018 and March 2019 with a suspicion of UTI were eligible for the study. Only confirmed cases presenting a positive urine culture with unique GNB were retained for further study analyses. Integrons were detected directly from urines using real-time PCR. Results: The data of 72 patients were analysed and integrons were detected in 15 urine samples. The negative predictive value of integron detection for resistance to trimethoprim/sulfamethoxazole was 100% as all of the GNB (all were Enterobacterales) isolated from patients with no integrons detected in their urine samples were susceptible to trimethoprim/sulfamethoxazole. Conclusions: The detection of integrons in cases of paediatric patients with suspected UTI could help limit 3GC empirical use and empower an empirical first-line strategy better tailored to the needs of each patient.